An audit of dental implants placed at the wits oral health centre - Desai, Nayan (My University, 2020)
Introduction; An implant supported prosthesis is a successful management option to replace missing teeth. Patient demand for implant supported dental prostheses is increasing due to growing awareness and greater aesthetic and functional expectations. A multitude of factors influence successful dental implant treatment outcomes. These include practitioner, patient, biological, hardware, biomechanical factors. The surgical departments of Oral Medicine and Periodontology (OMP) and Maxillofacial and Oral Surgery (MFOS) at the Wits Oral Health Centre (WOHC) are responsible for the surgical aspects of dental implantology. Rationale: The treatment trends and level of care in the practice of dental implantology has never been reviewed as a quality improvement process at the WOHC. Aim: The aim of the study was to report on implants placed at the WOHC over a 78-month period (January 2012-June 2018). Methods: The files of patients that received dental implants in the OMP and MFOS departments at WOHC were accessed and the relevant information was documented using a data collection sheet. Descriptive statistics of frequency, percentage, mean and standard deviation was used to summarise and present data. Chi-Square test was used to determine the association between categorical variables operator experience and early complications. Results: The study included 46 patients from the OMP department who collectively received 102 dental implants. The study recorded a 94.12% implant survival rate, with no association between operator experience and implant failure (p=0.82).There was also no significant association between operator experience and occurrence of a post-surgical complication (p=0.37). Conclusion: The implantology treatment outcomes are comparable with standard international practices and trends. The surgical skill of the registrars is satisfactory in relation to the occurrence of postsurgical complications and implant success. Further research dedicated to the influence of surgeon experience on surgical outcomes may be required
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Dentistry to the Faculty of Health Sciences, School of Oral Health Sciences, University of Witwatersrand, Johannesburg, 2020